NATIONAL-CULTURAL MARKEDNESS OF COLLOQUIAL VOCABULARY - Faleeva Anastasiya Vadimovna (Journal of Social Science, 2026)
Objective : The given article deals with the problem of national-cultural markedness of colloquial vocabulary as a functional-semantic and culture-specific, linguistically conditioned phenomenon reflecting the collective experience, social norms and culturally specific modes of conceptualization. Method : The article inspired by theoretical ideas from linguoculturology, sociolinguistics and pragmatics explores the national-cultural determinants of semantics, pragmatics and employs colloquial expressions in modern English language. Results : Evidence illustrates the codification of value judgments, social relationships, and shared background knowledge in terms of cultural coding in colloquial units. The results show that informal lexis is a major site of cultural specificity and until recently has been fraught with translation, lexicographic and cross-cultural issues. Novelty : They explore colloquial units both as informal lexical items and as the carriers of cultural meanings inscribed in everyday interaction.